PENGARUH PENAMBAHAN SUMBER PROTEIN NABATI BUNGKIL KELAPA TERHADAP PERTAMBAHAN BOBOT BADAN TERNAK KAMBING PERANAKAN ETTAWA (PE) - Hariyati Sarimo (Jambura Journal of Animal Science, 2019)
Hariyati Sarimo. 621415025. Effect of Addition of Coconut Vegetable Protein Source to the Increase in Weight of Ettawa (PE) Goat Breeding Body. Department of Animal Husbandry, Faculty of Agriculture, Gorontalo State University. Guided by Nibras Karnain Laya and Umbang Arif Rokhayati. The study aimed to determine body weight gain and feed conversion. This research was conducted in March 2019 - April 2019. The location of the study was conducted in Paris Village, Mootilango District, Gorontalo Regency. The study used 20 female ettawa (PE) Peranakan goats with age 2-3 years by providing forage feed and 50% coconut cake added. While processing data using the t test. The results showed that the addition of coconut cake was significantly different (P 0.05) to the value of the weight gain of ettawa goat breeds. where the average increase in body weight of ettawa Peranakan goat (PE) is 33 g / head / day. For feed conversion in ettawa (PE) crossbreed goats who were given an additional feed of coconut cake showed feed conversion of 0.18% and Etawa Peranakan goats given forage feed alone had a feed conversion value of 0.27%. The conclusion is that the addition of coconut cake was significantly different (P 0.05) on the increase in Ettawa (PE) goat body weight gain.